The role of Baitulmal towards the education of poor muslims in Sarawak - Dayang, Hummida; Mustafa Omar, Mohammed (2012)
Malaysia has a vision of becoming an international centre for education. It has formulated policies and programmes to achieve this noble vision. Several agencies have been established to operationalize these government educational programmes. In addition to these agencies, there are institutions that have also played remarkable roles towards education in Malaysia, notably the Baitulmal. The present study examines the role of Baitulmal towards educating poor Muslim students in Sarawak. Specifically, the study investigates the relationship between total expenditure growth rate of Baitulmal as dependent variable and five independent variables, which include the growth rates of total zakat collection, total expenditure on university student, total expenditure on secondary and primary student, total expenditure growth rate on university student and total expenditure growth rate on secondary and primary students. An Augmented-Dickey Fuller (ADF) unit root test, Johansen and Juselius cointegration approach and causality test based on Vector Error Correction Model (VECM) were employed to run the analysis using E-views software. The empirical evidences show that there exist causality effects between the growth rate of Baitulmal total expenditure and the growth rates of total collection of zakat, total expenditure on university students and, total expenditure on secondary and primary students, among others, in the estimation period. Thus, the results of the study indicate that Baitulmal has contributed significantly to the education of poor Muslims in Sarawak in the study period.